Research Progress of Nrf2 and Ferroptosis in Tumor Drug Resistance - Shuning HU; Xinru ZOU; Yixuan FANG; Chengrui LIU; Rui CHEN; Lili JI (Chinese Journal of Lung Cancer, 2023)
Lung cancer is one of the most common cancers in the world, and its treatment strategy is mainly surgery combined with radiotherapy and chemotherapy. However, long-term chemotherapy will result in drug resistance, which is also one of the difficulties in the treatment of lung cancer. Ferroptosis is an iron-dependent and lipid peroxidation-driven non-apoptotic cell death cascade, occurring when there is an imbalance of redox homeostasis in the cell. Nuclear factor erythroid 2-related factor 2 (Nrf2) is key for cellular antioxidant responses. Numerous studies suggest that Nrf2 assumes an extremely important role in regulation of ferroptosis, for its various functions in iron, lipid, and amino acid metabolism, and so on. In this review, a brief overview of the research progress of ferroptosis over the past decade will be presented. In particular, the mechanism of ferroptosis and the regulation of ferroptosis by Nrf2 will be discussed, as well as the role of the Nrf2 pathway and ferroptosis in tumor drug resistance, which will provide new research directions for the treatment of drug-resistant lung cancer patients.